Longitudinal assessments highlight long-term behavioural recovery in disorders of consciousness. Issue 1 (16th September 2019) - Bareham, Corinne A; Allanson, Judith; Roberts, Neil; Hutchinson, Peter J A; Pickard, John D; Menon, David K; Chennu, Srivas
Abstract: Accurate diagnosis and prognosis of disorders of consciousness is complicated by the variability amongst patients' trajectories. However, the majority of research and scientific knowledge in this field is based on cross-sectional studies. The translational gap in applying this knowledge to inform clinical management can only be bridged by research that systematically examines follow-up. In this study, we present findings from a novel longitudinal study of the long-term recovery trajectory of 39 patients, repeatedly assessed using the Coma Recovery Scale-Revised once every 3 months for 2 years, generating 185 assessments. Despite the expected inter-patient variability, there was a statistically significant improvement in behaviour over time. Further, improvements began approximately 22 months after injury. Individual variation in the trajectory of recovery was influenced by initial diagnosis. Patients with an initial diagnosis of unresponsive wakefulness state, who progressed to the minimally conscious state, did so at a median of 485 days following onset—later than 12-month period after which current guidelines propose permanence. Although current guidelines are based on the expectation that patients with traumatic brain injury show potential for recovery over longer periods than those with non-traumatic injury, we did not observe any differences between trajectories in these two subgroups. However, age was a significant predictor, with younger patients showing more promising recovery. Also, progressive increases in arousal contributed exponentially to improvements in behavioural awareness, especially in minimally conscious patients. These findings highlight the importance of indexing arousal when measuring awareness, and the potential for interventions to regulate arousal to aid long-term behavioural recovery in disorders of consciousness. Abstract : Patients with disorder of consciousness showed longitudinal improvements in behaviour consistent with a pattern of late recovery. Variability in recovery was predicted by initial diagnosis and age. It was progressively influenced by arousal, highlighting the importance of measuring arousal and the potential for arousal interventions to aid recovery. Graphical Abstract: